TRANSFORMASI MEDIA ISLAM DI ERA DIGITAL: (Studi Perkembangan Media Online Islam Indonesia Pasca Reformasi) - Lubis, Muhammad Rahmadani; Abdullah, Abdullah (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The transformation of Islamic media in the digital context shows a significant change in the way information is disseminated and public opinion is formed in Indonesia. After the reform era, the increase in press freedom and technological advances have encouraged the emergence of Islamic-based online media as one of the main communication channels for the people. This research aims to analyze the changes that occur in Islamic media, both in terms of content, platforms, and distribution strategies. The method used in this study is a qualitative approach with case studies on several leading Islamic online media in Indonesia. The findings of the study indicate that Islamic media has adapted to digital technology, including the use of social media and mobile applications, to reach a wider audience, especially among the younger generation. This transformation process is characterized by the diversification of content that includes religious, social, economic, and political issues, which is presented with a more inclusive and interactive approach. However, challenges such as polarization of opinions, the spread of misinformation, and the commodification of religion are also issues that need attention. This study concludes that Islamic online media has an important role in shaping Islamic identity and discourse in the digital era, but it is necessary to strengthen journalistic ethics and digital literacy to reduce the negative impact that may arise.